Differences and similarities between the symptoms and clinical signs in patients with pulmonary tuberculosis and pneumonia - smiljic, sonja; Radović, Blagica; Ilić, Aleksandra; Trajković, Goran; Savić, Sladjana; Milanović, Zvezdan; Mijović, Milica (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Tuberculosis in the second decade of the 21st century is an infectious disease with the highest mortality rate. In addition, in developed countries, pneumonia is the major couse of morbidity and mortality in adults. The aim of our study was to point out the differences and similarities between symptoms, laboratory parameters and clinical indicators in patients with pulmonary tuberculosis (PTB) and patients with pneumonia in the general population and in people belonging to the high risk groups for developing tuberculosis. Methods. This prospective study included patients with PTB (n = 70) and pneumonia (n = 75) treated at the Pulmonology Department of Clinical Hospital Center in Kosovska Mitrovica. Results. PTB was more frequent in men, 30–39 years of age (OR; 6:08), mainly from rural areas (p = 0.001), and with lower levels of education (p = 0.031). Pneumonia was more frequent in women older than 60 years of age (p = 0.0012). Night sweats (p = 0.001) and weight loss (p = 0.062) were significantly more frequent in patients with PTB, while chest pain (p = 0.001) and high temperature (p = 0.036) were more common in patients with pneumonia. X-ray changes in patients with PTB were located in the upper fields (p = 0.001), or appeared to be bilateral (p = 0.004). The strongest predictor associated with an increased risk of night sweats was diagnosed PTB (OR = 30.0). The chest pain was a predictor of pneumonia, unilateral changes (OR = 4.65) in the lower lung fields (OR = 0.08). Conclusion. Night sweats, weight loss and chest X-ray abnormalities in upper fields were significant indicators of PTB. Chest pain, fever and chest X-ray abnormalities in lower fields were significant indicators of pneumonia.
Keywords: tuberculosis, pulmonary; pneumonia; signs and symptoms; risk factors